Inventory Of Seafood Based Randang Recipes In Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan - Yessy Rahmadhani; Elida Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
This research was motivated because there was no research on seafood-based randang in Ranah Pesisir District, Pesisir Selatan Regency. There is a need for research to record village assets and because there is no book explaining the kinds of randang recipes and the processing of randang in Ranah Pesisir sub-district. The purpose of this study was to make an inventory of the kinds of randang recipes that included ingredients and spices, equipment and processing processes in Ranah Pesisir District. This type of research is qualitative. Data collection techniques by means of observation, interviews and documentation. Data analysis used in the field is data reduction, data presentation, conclusion and verification. The results of this study indicate that there are 6 kinds of randang made from seafood, namely fish randang, shrimp randang, lokan randang, crab randang, dry teri randang, squid randang. The ingredients for making seafood-based randang consist of fish, shrimp, lokan, crab, dried anchovies, squid. Supporting materials consist of fern leaves, Tapak Leman leaves, green beans, cassava leaves, coconut milk. The ingredients for making randang made from seafood consist of ground chilies, shallots, garlic, ginger, galangal, lemongrass, turmeric leaves, lime leaves, bay leaves, tamarind, salt, sugar, and spices which are used to make seafood-based randang, including coriander. Randang processing equipment made from seafood, namely stale Sanduak, stale cauldron, and stove. Randang processing is done traditionally using a stove and firewood until it is dry and blackish in color.